Empirical examination of the determinants of corruption: cross-sectional and panel analysis - El-Bahnasawy, Nasr Galal El-Din, author; Revier, Charles F., advisor; Bernasek, Alexandra, advisor (Colorado State University. Libraries, 2008)
This study explores the determinants of corruption, using cross-sectional, panel random-effects, and dynamic panel analysis to check the robustness of the results to alternative specifications and estimation methods. The study uses two different indexes of perceived corruption, the Corruption Perception Index (CPI) and the Control of Corruption measure (CC), to check the robustness of the results with alternative corruption measures. The study also uses a large array of explanatory variables that may influence corruption, including a large set of economic variables, a set of political variables, and a group of sociocultural variables. The first interesting result indicates that the rule of law strongly impacts corruption and that a better quality of law enforcement is correlated with lower corruption. Moreover, rich countries are perceived to have lower corruption than poor countries. This work highlights the importance of the rule of law and per capita GDP in the battle against corruption. Furthermore, this study finds the following. Lagged corruption impacts current level of corruption. Larger countries seem to have higher perceived corruption. A larger percentage of the population that is rural is associated with higher perceived corruption. Higher proportion of seats held by women in the national parliament is associated with lower corruption. Political stability, regulatory quality, ethnic fractionalization, and natural resource abundance do not impact corruption in my analysis. This study also examined the impact of some other factors on corruption such as voice and accountability, government effectiveness, the cost of business start-up procedures, the ratio of average government wage to per capita GDP, the degree of openness to international trade, membership in various religions, the level of economic development, and the legal system origin.
Keywords: corruption; determinants of corruption; gross domestic product; rule of law